Predictors of consistent condom use among young psychoactive substance users in Kampala's informal settlements, Uganda - Tonny Ssekamatte; Richard K. Mugambe; Aisha Nalugya; John Bosco Isunju; Joseph K.B. Matovu; Winnie K. Kansiime; Bonny E. Balugaba; Patience Oputan; Arnold Tigaiza; Solomon Tsebeni Wafula; Simon P.S. Kibira; Rhodah K. Wanyenze (Elsevier, 2022)
Introduction: The use of psychoactive substances increases the likelihood of unprotected sexual intercourse with individuals whose health status is not known, and consequently sexually transmitted infections, especially among young people. Despite this risk, there is limited evidence of the predictors of consistent condom use among young psychoactive substance users (YPSUs) in informal settings. This study examined the predictors of condom use among YPSUs in Kampala's informal settlements, Uganda. Methods: A cross-sectional study was conducted among 768 YPSUs. Respondent-driven sampling was used to recruit respondents. A structured questionnaire was used to collect respondent data on condom use. Data were analysed using Stata version 15.0. Prevalence ratios (PR) were used to determine the predictors of consistent condom use. Results: Out of the 744 YPSUs, only 37.4% of the respondents reported consistent condom use in the last 30 days. The prevalence of condom use was statistically lower among young people aged 20-24 years (35.4%) compared to those aged 18-19 years (43.7%), and among the married (17.3%) compared to respondents with a "single" marital status (43.0%). Being married (PR 0.42, 95% CI: 0.30-0.59), longer duration between meeting the most recent partner and having initial sexual contact with them (7 months to 1 year: PR 0.56, 95% CI: 0.36-0.88; more than a year: PR 0.36, 95% CI: 0.17-0.75) was negatively associated with consistent condom use. Spending less than 24 h between meeting the most recent partner and having initial sexual contact was positively associated with consistent condom use (PR 1.60, 95% CI: 1.24-2.08). Conclusion: The prevalence of consistent condom use in the last 30 days among YPSUs was low. Marital status and the duration between meeting the most recent partner and initial sexual contact predicted consistent condom use. There is a need to intensify awareness on the importance of consistent condom use among young people.